Banking system in Kyrgyz Republic - Lutfu Sagbansu (IBSU Scientific Journal (IBSUSJ), 2006)
This paper examines the overall banking system and the basic banking system development factors such as internet banking and deposit insurance in the world and particularly in Kyrgyzstan. The analyses show that progress in banking reform, introduction of deposit insurance and internet banking concepts are essential for avoiding harmful problems, development stable and solvent banking system. These developments include the more effective regulation of the entry and exit of banks, removal of obstacles to the expansion of foreign-owned banks and the transfer of technology and banking skills that expand access to finance, particularly by small and medium-sized enterprises.
Keywords: 330; Banking deposit insurance; Kyrgyzstan.